E-Wallet Usage Behavior: A Tam Approach And Success Model - Rachmasari, Annisa (The International Journal of Accounting and Business Society, 2023)
Purpose — This study was formulated to test and analyze the positive influence of the perception of usability, ease, satisfaction, and behavioral interest in using e-wallets. Design/methodology/approach—This research paradigm uses quantitative-type positivism with an exploratory approach. The population and sample were 363 respondents who were E-wallet users. Data analysis was using SEM-PLS. Findings —The results of this study succeeded in empirically proving that constructs in the TAM model (Davis et al., 1989) and satisfaction constructs (DeLone & McLean, 1992) can answer the behavioral problem of using e-wallets. In addition, this study can develop the concept of acceptance and success in using e-wallets, seen from the perspective of lecturers as e-wallet users. The development of the concept is carried out by testing the construct of perception of usefulness, perception of ease of use, behavioral interest, satisfaction, and actual use. Practical implications — In increasing the use of e-wallets, service providers and vendors must also consider and concentrate on building the ease of new services that will be issued. So that information technology, especially e-wallets, can be used or reached by all circles. Originality/value — This study seeks to combine the TAM Approach: Perceived Usefulness & Perceived ease of use, Behavior Intention, and Actual Use (Davis et al., 1989) with the Success Model: User Satisfaction (DeLone & McLean, 1992). Keywords — TAM Approach, Success Model. Paper type — Case study